Complete genome of the Medicago anthracnose fungus, Colletotrichum destructivum, reveals a mini-chromosome-like region within a core chromosome - Lapalu, Nicolas; Simon, Adeline; Lu, Antoine; Plaumann, Peter-Louis; Amselem, Joëlle; Pigné, Sandrine; Auger, Annie; Koch, Christian; Dallery, Jean Félix; O'connell, Richard J. (Microbial Genomics, 2024)
Colletotrichum destructivum (Cd) is a phytopathogenic fungus causing significant economic losses on forage legume crops (Medicago and Trifolium species) worldwide. To gain insights into the genetic basis of fungal virulence and host specificity, we sequenced the genome of an isolate from Medicago sativa using long-read (PacBio) technology. The resulting genome assembly has a total length of 51.7 Mb and comprises ten core chromosomes and two accessory chromosomes, all of which were sequenced from telomere to telomere. A total of 15, 631 gene models were predicted, including genes encoding potentially pathogenicity-related proteins such as candidate-secreted effectors (484), secondary metabolism key enzymes (110) and carbohydrate-active enzymes (619). Synteny analysis revealed extensive structural rearrangements in the genome of Cd rela-tive to the closely related Brassicaceae pathogen, Colletotrichum higginsianum. In addition, a 1.2 Mb species-specific region was detected within the largest core chromosome of Cd that has all the characteristics of fungal accessory chromosomes (transposon-rich, gene-poor, distinct codon usage), providing evidence for exchange between these two genomic compart-ments. This region was also unique in having undergone extensive intra-chromosomal segmental duplications. Our findings provide insights into the evolution of accessory regions and possible mechanisms for generating genetic diversity in this asexual fungal pathogen.
CRIS-Team Scopus Importer:2024-09-13
Keywords: accessory chromosome; chromosome rearrangements; fungal genomics; M. truncatula; phytopathogenic fungus; SD